Business strategy recommendation of pt edc indonesia to survive in geothermal tender stage - Ariani, Ariani; Anggoro, Yudo (The Indonesian Journal of Business Administration, 2016)
Abstract - The purpose of this research is to propose a new business strategy for company to survive in the industry. PT EDC Indonesia is an energy development company, which focus on geothermal resources and convert it to electricity. The company established in 2011 and already did 1 stage from geothermal development stage. Indonesia is the world's third largest geothermal electricity producer after United States and the Philippines and the second largest that have geothermal reserves. Indonesia holds 40% of the world's potential geothermal resources beneath thousand of volcanic islands and mountain. Although Indonesia has a huge geothermal potential, the utilization of geothermal energy is very low. Indonesia only utilizes 3.7% from their fully potential. However with the opportunity arises the company still aren't able to cultivate the geothermal resources. In dealing with challenges, some method is needed in order to perform PESTEL Analysis and Porter's Five Forces Analysis. Internal assessment was done using VRIO Framework, Market and Industry Analysis, and Resource Based View. Strategy formulation uses SPACE Matrix and QSPM with SWOT as an input. PT EDC Indonesia is in the quadrant IV and has four options of alternative strategies. Researchers are only taking two alternative strategies that support their research in accordance to their problems, which are intensive strategy and integrative strategy. To know these alternative strategies, the result QSPM is an intensive strategy. The next step is to analyze the Diamond Strategy to formulate new ideas that correspond to its functional strategy. In the end, this strategy will be implemented to follow and win the tender. The new strategy resulting from the analysis of this study including prepare all the data for preliminary survey, make computerized financial statement, prepare financial projections, and hire local experts employee. This strategy is implement to open a new geothermal concession that company will build to keep running in this industry.Â Keywords: business strategy, geothermal, diamond strategy